26th Annual Conference of the International Group for Lean Construction 2018
DOI: 10.24928/2018/0425
|View full text |Cite
|
Sign up to set email alerts
|

Can BIMFurnish Lean Benefits - an Indian Case Study

Abstract: Building Information Modelling (BIM) is recognized as an enabler for proficient accomplishment of projects in construction industry at different levels. Various benefits have been achieved globally through BIM implementations including enhanced visualization, collaboration between stakeholders throughout the project life cycle, time and cost savings, value engineering, change management and many others. Harnessing the BIM capabilities efficiently to gain maximum benefits on the projects can be a major mileston… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…For example, Building Information Modeling (BIM)based scheduling has been tied to scheduling (4D) in lean construction. Sacks et al (2009 and, in particular, and others (Mollasalehi, 2018;Singhal et. al., 2018;Fosse et al, 2017;Tillmann and Sargent, 2016;Dave et al, 2011, Teizer et al, 2017a have shown from the earliest concepts to now applications in industry.…”
Section: Tracking Methods For Lean Purposesmentioning
confidence: 90%
“…For example, Building Information Modeling (BIM)based scheduling has been tied to scheduling (4D) in lean construction. Sacks et al (2009 and, in particular, and others (Mollasalehi, 2018;Singhal et. al., 2018;Fosse et al, 2017;Tillmann and Sargent, 2016;Dave et al, 2011, Teizer et al, 2017a have shown from the earliest concepts to now applications in industry.…”
Section: Tracking Methods For Lean Purposesmentioning
confidence: 90%
“…This sample is listed in Table 6. Guidelines to develop a BIM model focused on construction planning and control [28] 10 Using technology to achieve lean objectives [56] 11 Development of an integrated BIM and lean maturity model [57] 12 CAN BIM furnish lean benefits-An Indian case study [58] 13 Envision of an integrated information system for project-driven production in construction [59] 14 Evaluation of a case study to design a BIM-based cycle planning concept [60] 15 An exploration of BIM and lean interaction in optimizing demolition projects [61] 16…”
Section: Final Sample Overviewmentioning
confidence: 99%
“…However, a synthesises of the two methodologies allows the full potential to be realized, i.e. to achieve improved project productivity, resource utilization and delivery times (Singhal et al, 2018;Fosse et al, 2017;Tillmann & Sargent, 2016). The combined use of LCM and modern technology has been the subject of several scientific studies and practical tests.…”
Section: Aim and Objectivesmentioning
confidence: 99%
“…So far, the solutions for possible interactions have been more theoretical. Recent studies, however, also analysed the possible interactions between LCM and BIM at trade contractor level (Tillmann & Sargent, 2016;Murphy et al, 2018;Singhal et al, 2018). A study by Fosse et al (2017) showed the results of the practical implementation of LCM and BIM by a Swedish contractor.…”
Section: Aim and Objectivesmentioning
confidence: 99%